Studies on chloroplast and nuclear rDNA in hexaploid bread wheat and its relatives - Rudnóy, Szabolcs (Acta Biologica Szegediensis, 2005)
Though allohexaploid bread wheat (Triticum aestivum) is grown on more acreage than any other cereal crop, its evolutionary history and origin of its three genomes have not been cleared up in every detail. The wheats form a polyploid series with diploid, tetraploid and hexaploid forms. Hexaploid wheats (AABBDD) may have evolved by hybridization between the AABB tetraploid as cytoplasm donor and the D genome diploid Aegilops tauschii. The origin of B genome is still a matter of debate. In the present study sequences of chloroplast and nuclear rDNA regions were used for giving new data to contribute to our knowledge on evolution of wheat. Analysis of cloned nrITS sequences of T. aestivum showed that 1) more than one ITS sequence type can be derived from the same sample, 2) a rye chromosome element formerly introgressed into wheat genome can be detected and 3) a partial segment of ITS similar to that of einkorn wheats (AA genome) can be identified. These results give evidences for ancient and recent introgressions and could help us to identify all of the three genomes of hexaploid bread wheat.